T2* - Personalized Trip Planner - Ferreira, J.; Martins, A. (Ambient Intelligence - Software and Applications - 8th International Symposium on Ambient Intelligence (ISAmI 2017), 2017)
In this research work we describe the framework for a Personalized Trip Planner identify as T2* (Travel to Anywhere) towards a digital concierge in everyone`s pocket by a tailor made aggregation of features and services. The mission is to empower key stakeholders in the travel and tourism industry (Travelers, Concierges, and Service Providers) to develop seamless travel experiences. This work is integrated with the MASAI H2020 project with the goal to serve in all stages of the travel process, including changes in travel-ers’ mobility patterns, associated local travel, long-distance travel, and busi-ness as well as to be used for leisure purposes. A personalized travel advice is produced based on the user’ profile created based on the user’ Facebook information extracted through a semantic approach. The quality of the ser-vice provided is measured and high-level service is promoted by an imple-mented reputation service.